THE PRESENT COLLAPSE OF ROMANIAN HIGHER EDUCATION. CAUSES AND EFFECTS - GABRIELA DUMBRAVĂ (Annals of the University of Petrosani: Economics)
The paper corroborates statistical data of economic and social nature in an attempt to outline the national and European context within which the Romanian educational system has constantly degraded over the past years. At the same time, the study exceeds the limits of a simple identification of causes and analyzes the collapse of higher education both as an ultimate consequence of governmental oblivion towards national education, and from the perspective of its devastating boomerang effect on the Romanian economy and on the society at large.